Injecting Joints and Tendons With Steroids - Gershon, Sydney L. (1983)
The local intra-articular injection of cortisone compounds is a dependable method for giving patients relief from the pain and swelling of arthritic joints. Injecting the diseased synovium surrounding a joint or tendon sheath or lining a bursa is usually an easy procedure, and the first injection has few contraindications if it is done cautiously. Many clinicians therefore readily embark upon treating patients with steroid injections. However, problems, including post-injection flares, infections and hematomata may begin about 12 hours after an injection. Indications and contraindications for administering injections are therefore discussed, and limitations and precautionary measures are explained.